Keberadaan bakteri dan perkembangan caecum akibat penambahan inulin dari umbi Dahlia (Dahlia variabilis) pada ayam kampung persilangan periode starter - Lilik Krismiyanto; Nyoman Sutama; Hanny Indrat Wahyuni (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2014)
The purpose of the research was to study the effects of feeding inulin derived from dahlia tuber powder and extract on the existence of bacteria and growth of caecum in crossbred native chicken starter period. Experimental animals were 280 birds of unsex crossbred native chicken and source of inulin derived from dahlia tuber in the form of powders and extract which were started to be fed on day 22. The present experiment was assigned in completely randomized design with 7 treatments and 4 replications (10 birds each). Feeding treatments were as follows: T0 (basal diet/BD), T1 (BD +0.4% powder of dahlia tuber), T2 (BD +0.8% powder of dahlia tuber), T3 (BD +1.2% powder of dahlia tuber), T4 (BD +0.39% extract of dahlia tuber), T5 (BD +0.78% extract of dahlia tuber) and T6 (BD +1.17% extract of dahlia tuber). Parameter measured were lactic acid bacteria (LAB), Escherichia coli, pH of caecum, height dan weight of caecum. Data were subjected to ANOVA and followed by Duncan. The results indicated that feeding inulin derived from dahlia tuber powder form at 0.8% (T2) and extract form at 1.17% (T6) could increase lactic acid bacteria population, low pH and Escherichia coli, increased height and weight of caecum. In conclusion, feeding inulin derived from dahlia tuber powder at 0.8% (T2) and extract formed at 1.17% (T6) could increase lactic acid bacteria, but on the contrary, it decreased intestinal pH and Escherichia coli population as well as increased height and weight of caecum. Keywords: crossbreed native chicken, inulin, caecum bacteria, caecum